2005
DOI: 10.1113/jphysiol.2005.084996
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional nutrition and the relationship between maternal body weight changes in the periconceptional period and feto‐placental growth in the sheep

Abstract: Recent studies in the sheep have shown that maternal undernutrition during the periconceptional period, when the nutrient demands of the embryo are minimal, can alter the subsequent development of the metabolic, endocrine and cardiovascular systems and that these effects may, in part, depend on embryo number. We have tested the hypotheses that there are relationships between maternal weight or body condition at the time of conception and feto-placental growth during the first 55 days of pregnancy, and that per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 27 publications
4
67
0
1
Order By: Relevance
“…Therefore, litter-size-dependent IUGR may result from failure of the uteroplacental complex fully to support growth of the multiple foetuses within the same uterus. Indeed, available evidence from studies of both sheep (Edwards and McMillen, 2002;Gardner et al, 2004;MacLaughlin et al, 2005) and humans (De Boo and Harding, 2006) suggests that reduced BWTs of individual lambs born in litters with more than one lamb have features in common with IUGR in lambs resulting from undernutrition, such as reduction in uterine blood flow per foetus and lower metabolite concentration in the maternal and foetal circulations. However, as ewes can clearly maintain a litter to term for which total weight approaches three times that of a normal single lamb (Dickinson et al, 1962), it is unclear why the individual BWTs of lambs born as twins or triplets are lower than those of lambs born as singletons.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, litter-size-dependent IUGR may result from failure of the uteroplacental complex fully to support growth of the multiple foetuses within the same uterus. Indeed, available evidence from studies of both sheep (Edwards and McMillen, 2002;Gardner et al, 2004;MacLaughlin et al, 2005) and humans (De Boo and Harding, 2006) suggests that reduced BWTs of individual lambs born in litters with more than one lamb have features in common with IUGR in lambs resulting from undernutrition, such as reduction in uterine blood flow per foetus and lower metabolite concentration in the maternal and foetal circulations. However, as ewes can clearly maintain a litter to term for which total weight approaches three times that of a normal single lamb (Dickinson et al, 1962), it is unclear why the individual BWTs of lambs born as twins or triplets are lower than those of lambs born as singletons.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal and neonatal body and brain weights are reduced in the 135 majority of these preclinical models, as is seen in human IUGR (Table 1, 2), although each model 136 affects neurodevelopment, and in turn cognitive outcomes to varying degrees. While there are 137 additional animal models of perturbed prenatal development in which neurodevelopment and/or 138 cognitive outcomes have been investigated, for example those investigating effects of 139 periconceptional and early gestational undernutrition in the sheep [76][77][78], these models do not 140 restrict fetal growth in late gestation or reduce size at birth as occur in human IUGR and are 141 therefore not discussed further in this review. Similarly, this review is limited to those models of 142 IUGR in which neurodevelopmental and/or cognitive outcomes have been reported.…”
Section: Introduction 32mentioning
confidence: 99%
“…Similarly, MacLaughlin et al (2005) reported that short-term undernutrition from 45 days before mating until 7 days after mating in singleton gestations did not affect uterine, fetal weights, weight of fetal membranes, placentome number, mean placentome weight and total placental weight at 53 to 56 days of pregnancy in the sheep. Quigley et al (2005) reported that maternal nutrition level in ewes during periconception period from 18 days before until 6 days after ovulation did not affect the primary fiber numbers of singleton fetus, but maternal over nutrition increased total muscle fiber numbers, secondary fiber numbers and secondary to primary fiber ratio in the ST muscles of singleton fetuses on day 75 of gestation compared with fetuses from undernutrition ewes.…”
Section: Figurementioning
confidence: 99%